Sustainability in hospitality and tourism sector - MERLY FISCAL ARJONA (Oakville, Ontario : Society Publishing, 2020)
Explains the ways in which people can achieve sustainability in the hospitality and tourism industry. The book also offers an introduction to sustainability, the principles to be followed to achieve sustainability in the hospitality industry, management of sustainability, and strategic marketing.
Keywords: Hospitality; Tourism